Monetary policy and the stock market in the euro area - Nuno Cassola; Claudio Morana (European Central Bank (ECB), 2002)
In this paper we study the role of the stock market in the transmission mechanism in the euro area and evaluate whether price stability and financial stability are mutually consistent and complementary objectives. Four major conclusions can be drawn from our work. First, stock prices and more generally, relative asset prices seem to play an important role in the transmission mechanism in the euro area. Second, we do not find any significant, direct impact of stock prices on inflation. These two findings taken together support the view that stock market prices may be important for monetary policy, independently of their direct impact on inflation. Third, permanent productivity shocks are the driving force of the stock market in the long-run and contribute significantly to its cyclical behaviour. Nevertheless, the bulk of cyclical dynamics in the stock market is explained by transitory shocks. Fourth, a monetary policy focused on maintaining price stability in the long-run can contribute also to stock market stability.
Keywords: C32; O11; 330; financial stability; Monetary policy transmission mechanism; price stability